FROM THE HISTORY OF THE FORMATION OF RUSSIAN VILLAGES IN THE FERGANA REGION (Scientific journal of the Fergana State University, 2026)
This article examines the organizational processes related to the creation of Russian villages from Russian citizens from various regions of the Russian Empire in the Fergana region, which was created in its place as a result of the occupation and liquidation of the Kokand Khanate by the Russian Empire, as well as the fact that by the end of the 19th century, the idea of strengthening the Russian state by relocating Russian nationalism to the occupied territories of Turkestan began to take root in the ruling circles of the Russian Empire, and special attention was paid to strengthening their administrative structures through the practice of resettling the population to the Fergana region, in addition, the peculiarities of resettling the resettled population to new places, issues related to the construction of Russian villages on so-calledempty state lands".